2019
DOI: 10.1002/jcb.28746
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine and organophosphorus pesticides and bladder cancer: A case‐control study

Abstract: Background Exposure to pesticides is associated with an increase in the incidence of cancer. We aimed to investigate the association of serum organochlorine pesticides (OCPs) and organophosphorus pesticides (OPs) levels and GSTM1/GSTT1 gene polymorphism with bladder cancer (BC). Methods This study was performed on 57 patients with BC and 30 controls (C). Acetylcholinesterase (AChE) activity, arylesterase activity of paraoxonase‐1 (ARE), total antioxidant capacity (TAC), and malondialdehyde (MDA) levels were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 61 publications
4
28
0
Order By: Relevance
“…In addition, the results manifested that the TAC levels and AChE activity were higher in the PTC group compared to the BTN group, indicating that the levels of OS were higher in the PTC group compared to the BTN group. It can be concluded that the OS levels depend on the type of pesticides as well as the amount and period of exposure, as reported previously (9)(10)(11)32).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In addition, the results manifested that the TAC levels and AChE activity were higher in the PTC group compared to the BTN group, indicating that the levels of OS were higher in the PTC group compared to the BTN group. It can be concluded that the OS levels depend on the type of pesticides as well as the amount and period of exposure, as reported previously (9)(10)(11)32).…”
supporting
confidence: 84%
“…OCPs disrupt human metabolism by increasing oxidative stress (OS) levels (9)(10)(11)(12). The loss of balance between the formation of reactive oxygen species (ROS) or nitrogen species (RNS) such as nitric oxide (NO) and the antioxidant defense mechanisms leads to a phenomenon called oxidative stress (OS) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lipophilicity, lindane can infiltrate and accumulate in the brain, human breast milk, and other organs that are rich in fat. Epidemiological and agricultural health studies reported that lindane exposure could be associated with the cancers of the breast, prostate, lung, stomach, colon, rectum, and bladder (Jayaraj et al, 2016;Abolhassani et al, 2019;Mortazavi et al, 2019).…”
Section: Toxicity Of Lindanementioning
confidence: 99%
“…aegypti [ 67 , 68 ]. Apart from resistance development, organophosphates are also implicated with severe adverse effects such as reduced antioxidant capacity, generation of free radicals, and inhibition of acetylcholinesterase and bladder cancer [ 69 , 70 ]. Long-term use of OP has resulted in the accumulation of its residues in water, soil, food, cow milk, and other environmental components [ 71 ].…”
Section: Discussionmentioning
confidence: 99%